Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine which of the expressions is equivalent to [tex]\( p \vee q \)[/tex] (which states "p or q"), let's analyze each of the given options in detail:
Option A: [tex]\( \neg p \rightarrow q \)[/tex]
To understand this, recall that the implication [tex]\( \neg p \rightarrow q \)[/tex] can be rewritten as [tex]\( \neg(\neg p) \vee q \)[/tex] using logical equivalences. Simplifying [tex]\( \neg(\neg p) \)[/tex] gives us [tex]\( p \vee q \)[/tex]. Therefore, [tex]\( \neg p \rightarrow q \)[/tex] is indeed equivalent to [tex]\( p \vee q \)[/tex].
Option B: [tex]\( \neg(\neg p \vee \neg q) \)[/tex]
This is the negation of the disjunction [tex]\( \neg p \vee \neg q \)[/tex]. According to De Morgan's laws, [tex]\( \neg(\neg p \vee \neg q) \)[/tex] is equivalent to [tex]\( p \wedge q \)[/tex] (the conjunction "p and q"), which is logically different from [tex]\( p \vee q \)[/tex].
Option C: [tex]\( \neg\left(p \wedge q\right) \)[/tex]
According to De Morgan's laws again, [tex]\( \neg(p \wedge q) \)[/tex] is equivalent to [tex]\( \neg p \vee \neg q \)[/tex]. This is clearly not the same as [tex]\( p \vee q \)[/tex].
Option D: [tex]\( \neg(p) \)[/tex]
This option is just the negation of [tex]\( p \)[/tex], which is unrelated to [tex]\( q \)[/tex]. Hence, it cannot be equivalent to [tex]\( p \vee q \)[/tex].
Given these analyses, the expression that is equivalent to [tex]\( p \vee q \)[/tex] is:
A. [tex]\( \neg p \rightarrow q \)[/tex]
Thus, the correct choice is Option A.
Option A: [tex]\( \neg p \rightarrow q \)[/tex]
To understand this, recall that the implication [tex]\( \neg p \rightarrow q \)[/tex] can be rewritten as [tex]\( \neg(\neg p) \vee q \)[/tex] using logical equivalences. Simplifying [tex]\( \neg(\neg p) \)[/tex] gives us [tex]\( p \vee q \)[/tex]. Therefore, [tex]\( \neg p \rightarrow q \)[/tex] is indeed equivalent to [tex]\( p \vee q \)[/tex].
Option B: [tex]\( \neg(\neg p \vee \neg q) \)[/tex]
This is the negation of the disjunction [tex]\( \neg p \vee \neg q \)[/tex]. According to De Morgan's laws, [tex]\( \neg(\neg p \vee \neg q) \)[/tex] is equivalent to [tex]\( p \wedge q \)[/tex] (the conjunction "p and q"), which is logically different from [tex]\( p \vee q \)[/tex].
Option C: [tex]\( \neg\left(p \wedge q\right) \)[/tex]
According to De Morgan's laws again, [tex]\( \neg(p \wedge q) \)[/tex] is equivalent to [tex]\( \neg p \vee \neg q \)[/tex]. This is clearly not the same as [tex]\( p \vee q \)[/tex].
Option D: [tex]\( \neg(p) \)[/tex]
This option is just the negation of [tex]\( p \)[/tex], which is unrelated to [tex]\( q \)[/tex]. Hence, it cannot be equivalent to [tex]\( p \vee q \)[/tex].
Given these analyses, the expression that is equivalent to [tex]\( p \vee q \)[/tex] is:
A. [tex]\( \neg p \rightarrow q \)[/tex]
Thus, the correct choice is Option A.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.